A Methyl‐Substituted Thiophene–Tetrathiafulvalene Donor and Its Salts. Issue 30 (22nd September 2015) - Silva, Rafaela A. L.; Santos, Isabel C.; Lopes, Elsa B.; Rabaça, Sandra; Galindo, Sergi; Mas‐Torrent, Marta; Rovira, Concepció; Almeida, Manuel; Belo, Dulce
Abstract: α‐Methyldithiophene–tetrathiafulvalene (α‐mDT‐TTF), the first alkyl‐substituted thiophene–tetrathiafulvalene electronic donor, and some of its charge‐transfer salts were explored. The crystal structure of α‐mDT‐TTF is composed of molecular stacks aligned parallel to each other. Its cyclic voltammetry shows higher electron‐donor ability than the unsubstituted analogue. This material was employed as a semiconductor in an organic field‐effect transistor and showed a mobility of 4 × 10 –4 cm 2 V –1 s –1 . Two charge‐transfer salts of this donor with [M(mnt)2 ] – anions (mnt = maleonitriledithiolate), M = Co and Au, were obtained by electrocrystallization; they present unusual stoichiometries: (α‐mDT‐TTF)[Co(mnt)2 ] and (α‐mDT‐TTF)3 [Au(mnt)2 ]2 . In the cobalt compound, the donor molecules are fully oxidized and the Co complex is dimerized; it presents semiconducting behavior (7 × 10 –3 S cm –1 ). The gold compound is composed of alternating stacks of donor trimers and pairs of anions. Abstract : α‐Methyldithiophene–tetrathiafulvalene has lower oxidation potentials than the unsubstituted analogue and shows a mobility of 4 × 10 –4 cm 2 V –1 s –1 if used as a semiconductor in an organic field‐effect transistor. Two charge‐transfer salts are obtained by electrocrystallization; they present unusual stoichiometries and interesting crystal structures that are modulated by the donor's methyl group.